2020
DOI: 10.2174/1574886314666191008095344
|View full text |Cite
|
Sign up to set email alerts
|

Current Disposal Practices of Unused and Expired Medicines Among General Public in Delhi and National Capital Region, India

Abstract: Background: Stocking unused or expired medicines or donating these to others can lead to accidental or inappropriate ingestion, increasing the risk of adverse drug reaction(s) and even lead to antibiotic resistance. Further improper disposal of expired or unused medicines is associated with environmental pollution, health hazards and damage to ecosystem. Ecopharmacovigilance is an important area in this context. Objective: To explore the awareness and disposal practices of unused/expired in the general publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 17 publications
6
20
0
2
Order By: Relevance
“…In the present study, throwing away the medicines in household garbage and flushing in toilet/sink were the most commonly preferred disposal practices for both unused and expired medicines. The finding is in agreement with studies conducted in Ethiopia [16,34] and elsewhere in the world [4,6,20,21,31,35]. In our study, burning leftover medicines were the other means of disposing for both unused and expired household medicines as reported by nearly twothirds of the respondents.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, throwing away the medicines in household garbage and flushing in toilet/sink were the most commonly preferred disposal practices for both unused and expired medicines. The finding is in agreement with studies conducted in Ethiopia [16,34] and elsewhere in the world [4,6,20,21,31,35]. In our study, burning leftover medicines were the other means of disposing for both unused and expired household medicines as reported by nearly twothirds of the respondents.…”
Section: Discussionsupporting
confidence: 93%
“…"Drug Disposal Day" could be a practical approach for taking back medicine [69]. Another study in India revealed that 96% of consumers threw away expired medication, and 73% were discarded in household trash with other garbage [70], supported by another study of Australia and Ethiopia [71,72]. According to this study, 72% of respondents emphasized safe drug disposal similarity with a study of Malaysia for household pharmaceutical waste (HPW) [73] and a similar study reported in Poland and Lebanon [74,75].…”
Section: Discussionsupporting
confidence: 67%
“…Other studies have also reported a high proportion of storage of unused and expired medicines in households. [22][23][24] Regarding the risks of storing unused and expired medicines in their homes, 350 (90.9%) of participants strongly agreed that children are more susceptible to the risks related to unused and expired household medicines. Accidental pharmaceutical poisoning in young children is common and therefore, the need to appropriately store and safely dispose of unused and expired medicines.…”
Section: Discussionmentioning
confidence: 99%